Studying the impact of remote physical education classes on the functional state of the cardiorespiratory system and physical health of female students aged 17-19 - Pavelko , O.; Svatiev , A. (Sportyvnyi Visnyk Prydniprovia, 2024)
Introduction and purpose of the study. The article is devoted to the study of the peculiarities of the dynamics of indicators of functional state of circulatory systems, external respiration and physical health of students of 17-19 years of higher education in the process of physical education classes online under the program developed by us. In the course of the study, it was important to show the impact of the proposed program of distance education on the functional state and the level of physical health of students of university, which are considered as one of the most objective criteria for its effectiveness. The research hypothesis is the need to develop new distance training programs for students and students of higher education in connection with modern living conditions (quarantine restrictions and martial law). The goal is to study the peculiarities of changes in the functional state of circulatory systems and external respiration and physical health of students 17-19 years during the school year under the influence of the experimental program of remote physical education. Materials and methods. The results of testing the functional state of circulatory systems, external respiration and physical health are generalized in the work of 33 students of 17-19 years of higher education at different stages of the academic year, which were engaged in the developed program of distance training on physical education. Results. The peculiarities of the dynamics of indicators of functional state of circulatory systems, external respiration and physical health of students 17-19 years in the process of annual physical education classes in remote form under the program developed by us. It was proved that the completion of the study in girls had positive changes in some indicators of the functional state of the cardiovascular system by 4-12%, external respiration system by 5-30%and physical health level by 15%. It should be noted that significant changes have been registered only for certain indicators of functional status and physical health of the subjects of the subject. Conclusions: At the beginning of the study of the magnitude of students of 17-19 years, there was a reduced level of functional state of circulatory systems, external respiration and physical health. The magnitudes of most parameters of these systems were considered as medium and below average. The use in the educational process of the proposed program of remote physical education classes has contributed to the improvement of certain indicators of the cardiorespiratory system and physical health. The results obtained testified to the eficiency of the developed program of physical education for students for 17-19 years, but minor positive changes in most indicators of the functional state of the cardiorespiratory system of their organism and physical health indicated the need for further correction Higher education students.